Easily-slit anisotropic conductive adhesive film and preparation method thereof
By using a combination of low-boiling and high-boiling solvents, as well as ultra-low Tg acrylate prepolymer and silane coupling agent, the peeling force between the heterosquamous conductive adhesive film and the protective film is improved, and the uneven edges and inverse edges during the slitting process are solved. The peeling problem achieves easy slitting effect.
Patent Information
- Application Number
- CN202411180599.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-27
AI Technical Summary
The peeling force between the existing heterosqualitative conductive adhesive film and the protective film during the slitting process is insufficient, resulting in uneven edges and reverse peeling, affecting product performance.
Using a combination of low-boiling organic solvents and high-boiling ester solvents, combined with ultra-low Tg acrylate prepolymer and silane coupling agent, the peeling force between ACF and the protective film is improved, and the solvent residue is ensured through appropriate coating temperature and time. Within suitable range.
The peeling force between ACF and the protective film is significantly improved, achieving easy slitting effect, ensuring neat edges and stable performance of the product.
Smart Images

Figure BDA0005012031480000081 
Figure BDA0005012031480000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive adhesive films, and relates to an easily slitting anisotropic conductive adhesive film and a preparation method thereof. Background Art
[0002] Anisotropic Conductive Film (ACF) is a special electronic connection material. Its unique anisotropic conductive properties play an important role in the electronics manufacturing industry. This feature is specifically manifested in that it only exhibits high conductivity in the vertical direction, while maintaining good insulation in the horizontal direction, thereby ensuring precise electrical connection while avoiding unnecessary short-circuit risks. This feature greatly expands its application scope in the field of precision electronic assembly. ACF is a composite material mainly composed of conductive particles and adhesives, in which the conductive particles are responsible for providing conductive channels in the vertical direction. After applying pressure and heat, these particles can be precisely aligned in the vertical direction to form an efficient conductive path to ensure smooth current flow. The main function of the adhesive is to fix the conductive particles between the two connected objects and provide stable electrical and mechanical connections. It must have excellent bonding strength, flexibility and weather resistance to adapt to the challenges of different material surfaces and complex use environments.
[0003] The preparation process of anisotropic conductive film includes three steps: mixing, coating, and slitting. During the mixing process, each component is added to the solvent to fully mix the formula components. The choice of solvent is very important. It is not only necessary to ensure that all components can be evenly dispersed, but also to consider the volatility in the subsequent processing process; during the coating process, the ACF slurry is evenly coated on the protective film; after the coating is completed, the composite film needs to be cut into products of the required size by a slitting machine. During the slitting process, if the peeling force between the ACF and the protective film is low, then when the knife is used for cutting, the ACF may separate from the protective film, causing uneven edges (i.e. burrs), and reverse peeling may occur in subsequent use, affecting the performance of the final product. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides an easily slit anisotropic conductive adhesive film, which effectively improves the peeling force between the ACF and the protective film and realizes easy slitting of the ACF.
[0005] One object of the present invention is achieved by the following technical solutions:
[0006] An easily slitting anisotropic conductive adhesive film, the preparation raw materials of which include 30 to 50 parts of low boiling point organic solvent, 2 to 15 parts of high boiling point organic solvent, 20 to 45 parts of acrylate prepolymer, 1 to 10 parts of conductive particles, 5 to 15 parts of acrylate monomer, and 1 to 10 parts of free radical initiator;
[0007] The boiling point of low-boiling point organic solvents is ≤100°C, and the boiling point of high-boiling point organic solvents is ≥200°C.
[0008] Preferably, the boiling point of the low boiling point organic solvent is 40 to 90°C.
[0009] More preferably, the low boiling point organic solvent is one or more of butanone, acetone, ethyl acetate and the like.
[0010] Preferably, the boiling point of the high boiling point organic solvent is 200-250°C.
[0011] More preferably, the high boiling point organic solvent is an ester solvent having a boiling point of 200 to 250°C.
[0012] More preferably, the high boiling point organic solvent is one or more of a dimethyl diacid mixture (DBE), ethyl benzoate, isopropyl benzoate, dibutyl oxalate, amyl lactate and the like.
[0013] The dimethyl diacid ester mixture (DBE) is a mixture of dimethyl succinate, dimethyl glutarate and dimethyl adipate.
[0014] Preferably, the acrylate prepolymer is one or more of polyester acrylate, polyurethane acrylate, epoxy acrylate, and polysiloxane acrylate.
[0015] Preferably, the acrylate prepolymer includes an ultra-low Tg acrylate prepolymer with a glass transition temperature (Tg) ≤ 0°C, a medium Tg acrylate prepolymer with a Tg of 50-80°C, and a high Tg acrylate prepolymer with a Tg of 100-140°C.
[0016] Preferably, the acrylate prepolymer comprises 10 to 30 parts of ultra-low Tg acrylate prepolymer, 3 to 10 parts of medium Tg acrylate prepolymer and 3 to 10 parts of high Tg acrylate prepolymer.
[0017] Preferably, the mass of the ultra-low Tg acrylate prepolymer is ≥ the sum of the masses of the medium Tg acrylate prepolymer and the high Tg acrylate prepolymer.
[0018] The conductive particles are not particularly limited, and any conductive particles that can be used in anisotropic conductive films and have a conductive effect can be used. Preferably, the conductive particles are a core-shell structure composition with a polymer as the core and a metal layer as the shell. The polymer can be one or more of polymethyl methacrylate, polyaniline, polystyrene, polyacrylamide, polyvinyl chloride, and polyacrylonitrile, and the metal layer can be one or more of a nickel layer, a gold layer, a copper layer, and a cobalt layer. More preferably, the particle size of the conductive particles is 0.5 to 20 μm, and further 3 to 10 μm.
[0019] Preferably, the free radical initiator includes one or more of a peroxide initiator (such as benzoyl peroxide, potassium persulfate, ammonium persulfate, etc.), an azo initiator (such as azobisisobutyronitrile, diisopropyl azodicarboxylate, etc.) and a redox system initiator. The redox system initiator is composed of an oxidant (such as peroxide) and a reductant (such as ferrous sulfate, ascorbic acid, aluminum isopropoxide, etc.).
[0020] Preferably, the raw materials for preparation further include 5 to 20 parts of nitrile rubber, 5 to 25 parts of thermoplastic resin, 0.1 to 2 parts of silane coupling agent, 10 to 40 parts of inorganic filler, and 0 to 20 parts of other additives.
[0021] Preferably, the thermoplastic resin includes but is not limited to one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyurethane, polysulfone (PSF), polyethersulfone (PES), polyphenylene ether, polyamide, acrylonitrile-butadiene-styrene (ABS), styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), styrene-isoprene-styrene block copolymer (SIS), etc.
[0022] Preferably, the silane coupling agent includes one or more of vinyl type (such as vinyl triethoxysilane), chloroalkyl type (γ-chloropropyl triethoxysilane), aminoalkyl type (such as 3-aminopropyl triethoxysilane KH-550), epoxyalkyl type (such as γ-glycidyloxypropyl trimethoxysilane KH-560), and methacrylic acid acyloxyalkyl type (such as γ-methacrylic acid acyloxypropyl trimethoxysilane KH-570).
[0023] Preferably, the inorganic filler includes one or more of silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide and magnesium oxide.
[0024] There is no particular limitation on other additives, and any additive that can be used in the anisotropic conductive adhesive film to modify its functions may be used, and examples thereof include colorants, adhesion promoters, antioxidants, flame retardants, and the like.
[0025] The second object of the present invention is achieved by the following technical solutions:
[0026] A method for preparing anisotropic conductive adhesive film which is easy to cut comprises the following steps: mixing preparation raw materials to form a coating liquid, coating the coating liquid on a protective film, and cutting to obtain the anisotropic conductive adhesive film loaded on the protective film.
[0027] Preferably, the protective film is a polyimide film and / or a polyester film.
[0028] Examples of the polyester include one or more of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), poly(1,4-cyclohexanedimethylene terephthalate) (PCT), and polyethylene naphthalate (PEN).
[0029] Preferably, the raw materials are mixed at 10-40°C.
[0030] Preferably, the coating temperature is 65-75° C., and the coating time is 2-10 min.
[0031] Preferably, the residual solvent rate in the anisotropic conductive adhesive film supported on the protective film is greater than 4%, and the peeling force between the anisotropic conductive adhesive film and the protective film is greater than 10 gf / inch.
[0032] Residual solvent ratio = residual amount of organic solvent in the anisotropic conductive adhesive film / weight of the anisotropic conductive adhesive film * 100%.
[0033] More preferably, the residual solvent ratio in the anisotropic conductive adhesive film supported on the protective film is 4.1-8%, and the peeling force between the anisotropic conductive adhesive film and the protective film is 10.1-20 gf / inch.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The present invention adopts a low boiling point solvent with a boiling point of ≤100°C and a high boiling point ester solvent with a boiling point of ≥200°C, wherein the low boiling point solvent evaporates quickly, making the coating speed faster, and the high boiling point ester solvent makes it difficult for the solvent to evaporate from the ACF, and the ester solvent has better compatibility with acrylic ACF, and is less likely to evaporate from the ACF, so that the solvent residual rate is kept within a certain range.
[0036] 2. The present invention also uses an ultra-low Tg acrylate prepolymer with a Tg≤0°C. At a certain solvent residual rate, the residual solvent combines with the ultra-low Tg acrylate prepolymer to improve the wettability of the chain segments of the ultra-low Tg acrylate prepolymer and improve its adhesion to the protective film. If the solvent residual rate is too low, there is not enough solvent to wet the chain segments of the ultra-low Tg acrylate prepolymer, which will cause the adhesion between the ACF and the protective film to decrease.
[0037] 3. The ACF formula of the present invention also includes a silane coupling agent, which is also beneficial to improving the peeling force between the ACF and the protective film.
[0038] 4. The coating temperature of the present invention is between 65 and 75°C. If the temperature is too high, the solvent will volatilize excessively during the coating process, and the peeling force will be reduced; if the temperature is too low, too much solvent will remain in the ACF, causing the ACF colloid to be soft, and the knife will stick during slitting, resulting in slitting NG.
[0039] In summary, the present invention adds ultra-low Tg (≤0°C) acrylate prepolymer to the ACF formula, and increases the peeling force between the ACF and the protective film by mixed coating with a high boiling point (≥200°C) ester solvent and a low boiling point (≤100°C) solvent, thereby achieving an effect of easy cutting. DETAILED DESCRIPTION
[0040] The technical scheme of the present invention is further described below by specific embodiments. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not intended to be used for specific limitations of the present invention. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0041] In the following examples and comparative examples, the main raw materials are from the following sources:
[0042] Nitrile rubber: Lanzhou Petrochemical NBR 1906;
[0043] Thermoplastic resin: SBS resin, Kraton D1155;
[0044] Conductive particles: nickel-plated polystyrene microspheres, average particle size 5 μm, Zhenjiang Aibang Ni-500.
[0045] High Tg acrylate prepolymer: aliphatic polyurethane acrylate, Changxing 61857, Tg is 111.3℃;
[0046] Medium Tg acrylate prepolymer: polyurethane acrylate, Changxing 63158, Tg is 74.2℃;
[0047] Low Tg acrylate prepolymer: aliphatic polyurethane acrylate, Changxing DR-U356, Tg is 32.3℃;
[0048] Ultra-low Tg acrylate prepolymer: aliphatic polyurethane acrylate, Changxing 6113, Tg is -60.8℃;
[0049] Acrylate monomer: SR268, Sartomer;
[0050] Silane coupling agent: 3-aminopropyltriethoxysilane KH-550 and γ-glycidyloxypropyltrimethoxysilane KH-560 were purchased from Shandong Hengyu New Materials Co., Ltd.
[0051] Example 1
[0052] The raw materials for preparing the anisotropic conductive adhesive film of this embodiment include:
[0053] 10 parts of high boiling point solvent ethyl benzoate, 40 parts of low boiling point solvent butanone, 15 parts of ultra-low Tg acrylate prepolymer (Tg is -60.8°C), 5 parts of medium Tg acrylate prepolymer (Tg is 74.2°C), 5 parts of high Tg acrylate prepolymer (Tg is 111.3°C), 12 parts of nitrile rubber, 18 parts of thermoplastic resin, 10 parts of acrylate monomer, 1 part of silane coupling agent KH-550, 5 parts of conductive particles, 15 parts of silicon dioxide, 3 parts of titanium dioxide, and 2 parts of benzoyl peroxide.
[0054] The anisotropic conductive film of this embodiment is prepared by the following steps:
[0055] The raw materials were weighed according to the above weight parts and stirred at 30° C. to form a coating liquid. The coating liquid was coated on a PET film at 70° C. (3 min). After cutting, an anisotropic conductive adhesive film loaded on the PET film was obtained.
[0056] Example 2
[0057] The difference between Example 2 and Example 1 is that the raw materials for preparing Example 2 include:
[0058] 10 parts of high boiling point solvent ethyl benzoate, 40 parts of low boiling point solvent butanone, 5 parts of ultra-low Tg acrylate prepolymer (Tg is -60.8°C), 5 parts of medium Tg acrylate prepolymer (Tg is 74.2°C), 15 parts of high Tg acrylate prepolymer (Tg is 111.3°C), 12 parts of nitrile rubber, 18 parts of thermoplastic resin, 10 parts of acrylate monomer, 1 part of silane coupling agent KH-550, 5 parts of conductive particles, 15 parts of silicon dioxide, 3 parts of titanium dioxide, and 2 parts of benzoyl peroxide.
[0059] The rest is the same as Example 1.
[0060] Example 3
[0061] The difference between Example 3 and Example 1 is that the raw materials for preparing Example 3 include:
[0062] 10 parts of high boiling point solvent ethyl benzoate, 40 parts of low boiling point solvent butanone, 5 parts of ultra-low Tg acrylate prepolymer (Tg is -60.8°C), 15 parts of medium Tg acrylate prepolymer (Tg is 74.2°C), 5 parts of high Tg acrylate prepolymer (Tg is 111.3°C), 12 parts of nitrile rubber, 18 parts of thermoplastic resin, 10 parts of acrylate monomer, 1 part of silane coupling agent KH-550, 5 parts of conductive particles, 15 parts of silicon dioxide, 3 parts of titanium dioxide, and 2 parts of benzoyl peroxide.
[0063] The rest is the same as Example 1.
[0064] Example 4
[0065] The raw materials for preparing the anisotropic conductive adhesive film of this embodiment include:
[0066] 7 parts of high boiling point solvent dibutyl oxalate, 44 parts of low boiling point solvent acetone, 17 parts of ultra-low Tg acrylate prepolymer (Tg is -60.8°C), 6 parts of medium Tg acrylate prepolymer (Tg is 74.2°C), 7 parts of high Tg acrylate prepolymer (Tg is 111.3°C), 8 parts of nitrile rubber, 24 parts of thermoplastic resin, 8 parts of acrylate monomer, 1.5 parts of silane coupling agent KH-560, 7 parts of conductive particles, 12 parts of silicon dioxide, 6 parts of titanium dioxide, and 3 parts of benzoyl peroxide.
[0067] The anisotropic conductive film of this embodiment is prepared by the following steps:
[0068] The raw materials were weighed according to the above weight parts and stirred at 30° C. to form a coating liquid. The coating liquid was coated on a PET film at 75° C. (3 min). After cutting, an anisotropic conductive adhesive film loaded on the PET film was obtained.
[0069] Example 5
[0070] The raw materials for preparing the anisotropic conductive adhesive film of this embodiment include:
[0071] 12 parts of high boiling point solvent isopropyl benzoate, 35 parts of low boiling point solvent ethyl acetate, 19 parts of ultra-low Tg acrylate prepolymer (Tg is -60.8°C), 5 parts of medium Tg acrylate prepolymer (Tg is 74.2°C), 3 parts of high Tg acrylate prepolymer (Tg is 111.3°C), 13 parts of nitrile rubber, 15 parts of thermoplastic resin, 12 parts of acrylate monomer, 0.8 parts of silane coupling agent KH-550, 4 parts of conductive particles, 16 parts of silicon dioxide, 2 parts of titanium dioxide, and 1.5 parts of benzoyl peroxide.
[0072] The anisotropic conductive film of this embodiment is prepared by the following steps:
[0073] The raw materials were weighed according to the above weight parts and stirred at 30° C. to form a coating liquid. The coating liquid was coated on a PET film at 65° C. (3 min). After cutting, an anisotropic conductive adhesive film loaded on the PET film was obtained.
[0074] Comparative Example 1
[0075] The difference between Comparative Example 1 and Example 1 is that the solvents in Comparative Example 1 are all low-boiling point solvents, that is, the preparation raw materials of Comparative Document 1 do not include a high-boiling point solvent, but include 50 parts of a low-boiling point solvent butanone.
[0076] The rest is the same as Example 1.
[0077] Comparative Example 2
[0078] The difference between Comparative Example 2 and Example 1 is that the solvents in Comparative Example 2 are all high-boiling point solvents, that is, the preparation raw materials of Comparative Document 2 do not include low-boiling point solvents, but include 50 parts of high-boiling point solvent ethyl benzoate.
[0079] The rest is the same as Example 1.
[0080] Comparative Example 3
[0081] The difference between Comparative Example 3 and Example 1 is that the solvent in Comparative Example 3 is not the high boiling point solvent ethyl benzoate and the low boiling point solvent but 50 parts of toluene. The rest is the same as Example 1.
[0082] Comparative Example 4
[0083] The difference between Comparative Example 4 and Example 1 is that the solvent in Comparative Example 4 is not the high boiling point solvent ethyl benzoate and the low boiling point solvent but methyl ethyl ketone, but 50 parts of butyl acetate. The rest is the same as Example 1.
[0084] Comparative Example 5
[0085] The raw materials for preparing the anisotropic conductive adhesive film of Comparative Example 5 include:
[0086] 10 parts of high boiling point solvent ethyl benzoate, 40 parts of low boiling point solvent butanone, 20 parts of medium Tg acrylate prepolymer (Tg is 74.2°C), 5 parts of high Tg acrylate prepolymer (Tg is 111.3°C), 12 parts of nitrile rubber, 18 parts of thermoplastic resin, 10 parts of acrylate monomer, 1 part of silane coupling agent KH-550, 5 parts of conductive particles, 15 parts of silicon dioxide, 3 parts of titanium dioxide, and 2 parts of benzoyl peroxide. Others are the same as in Example 1.
[0087] Comparative Example 6
[0088] The raw materials for preparing the anisotropic conductive adhesive film of Comparative Example 6 include:
[0089] 10 parts of high boiling point solvent ethyl benzoate, 40 parts of low boiling point solvent butanone, 5 parts of medium Tg acrylate prepolymer (Tg is 74.2°C), 20 parts of high Tg acrylate prepolymer (Tg is 111.3°C), 12 parts of nitrile rubber, 18 parts of thermoplastic resin, 10 parts of acrylate monomer, 1 part of silane coupling agent KH-550, 5 parts of conductive particles, 15 parts of silicon dioxide, 3 parts of titanium dioxide, and 2 parts of benzoyl peroxide. The rest is the same as in Example 1.
[0090] Comparative Example 7
[0091] The raw materials for preparing the anisotropic conductive adhesive film of Comparative Example 7 include:
[0092] 10 parts of high boiling point solvent ethyl benzoate, 40 parts of low boiling point solvent butanone, 15 parts of low Tg acrylate prepolymer (Tg is 32.3°C), 5 parts of medium Tg acrylate prepolymer (Tg is 74.2°C), 5 parts of high Tg acrylate prepolymer (Tg is 111.3°C), 12 parts of nitrile rubber, 18 parts of thermoplastic resin, 10 parts of acrylate monomer, 1 part of silane coupling agent KH-550, 5 parts of conductive particles, 15 parts of silicon dioxide, 3 parts of titanium dioxide, and 2 parts of benzoyl peroxide. The rest is the same as in Example 1.
[0093] The residual solvent ratio in the anisotropic conductive adhesive films of the examples and comparative examples was measured, and the peeling force between the ACF and the PET film was measured at 180° peeling (300 mm / min). The results are shown in Table 1.
[0094] Table 1 Solvent residual rate of the embodiment and the comparative example and the peeling force between ACF and PET film
[0095]
[0096]
[0097] *4%<solvent residual rate<8% is qualified.
[0098] **10gf / inch<ACF and PET peeling force<20gf / inch, which means it is easy to cut.
[0099] As can be seen from Table 1, the ACF solvent residual rate of Examples 1-5 is greater than 4%. Under a certain solvent residual, the ultra-low Tg acrylate prepolymer combines with the solvent, making the chain segment wettability of the ultra-low Tg acrylate prepolymer better, the adhesion to PET is increased, and the ACF loaded on the PET film is easy to cut. Among them, the ultra-low Tg acrylate prepolymer content of Examples 2-3 is relatively low, and the peeling force between ACF and PET is reduced compared with Example 1.
[0100] Comparative Example 1 does not add a high boiling point solvent, and the low boiling point solvent is volatile, resulting in a low solvent residual rate of ACF. When the solvent residual rate is low, there is not enough solvent to wet the chain segments of the ultra-low Tg acrylic prepolymer, which greatly reduces the adhesion between ACF and PET. The ACF loaded on the PET film will form burrs when slitting. Comparative Example 2 does not add a low boiling point solvent, and the solvent residual rate is high at the same coating speed, resulting in a soft ACF colloid, which sticks to the knife during slitting and causes NG slitting. Reducing the coating speed can reduce the solvent residual rate, but it seriously affects the production capacity. Comparative Examples 3 and 4 use solvents with a boiling point of more than 100 degrees, and the solvent residual rate of ACF is still low, and the adhesion between ACF and PET is greatly reduced.
[0101] In Comparative Examples 5 and 6, no ultra-low Tg acrylic prepolymer was added. In the presence of only medium Tg acrylic prepolymer and high Tg acrylic prepolymer, even if the ACF had a qualified solvent residual rate, the adhesion between the ACF and PET was still greatly reduced. In Comparative Example 7, an acrylic prepolymer with a Tg of 32.3°C was added to replace the ultra-low Tg acrylic prepolymer. The adhesion between the ACF and PET was low, and there would be burrs after slitting.
[0102] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0103] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0104] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. An easily slitting anisotropic conductive adhesive film, characterized in that: The raw materials for preparing the anisotropic conductive adhesive film include 30 to 50 parts of low boiling point organic solvent, 2 to 15 parts of high boiling point organic solvent, 20 to 45 parts of acrylate prepolymer, 1 to 10 parts of conductive particles, 5 to 15 parts of acrylate monomer, and 1 to 10 parts of free radical initiator; The boiling point of low-boiling point organic solvents is ≤100°C, and the boiling point of high-boiling point organic solvents is ≥200°C.
2. The easily slitting anisotropic conductive adhesive film according to claim 1, characterized in that: The boiling point of low boiling point organic solvents is 40-90°C; And / or, the boiling point of the high boiling point organic solvent is 200 to 250°C.
3. The easily slitting anisotropic conductive adhesive film according to claim 1 or 2, characterized in that: The low boiling point organic solvent is one or more of butanone, acetone and ethyl acetate; And / or, the high boiling point organic solvent is one or more of a dimethyl diacid mixture, ethyl benzoate, isopropyl benzoate, dibutyl oxalate, and amyl lactate.
4. The easily slitting anisotropic conductive adhesive film according to claim 1, characterized in that: The acrylate prepolymer includes an ultra-low Tg acrylate prepolymer with a Tg of ≤0°C, a medium Tg acrylate prepolymer with a Tg of 50 to 80°C, and a high Tg acrylate prepolymer with a Tg of 100 to 140°C.
5. The easily slitting anisotropic conductive adhesive film according to claim 4, characterized in that: The mass of the ultra-low Tg acrylate prepolymer is ≥ the sum of the masses of the medium Tg acrylate prepolymer and the high Tg acrylate prepolymer.
6. The easily slitting anisotropic conductive adhesive film according to claim 1, characterized in that: The preparation raw materials also include 5 to 20 parts of nitrile rubber, 5 to 25 parts of thermoplastic resin, 0.1 to 2 parts of silane coupling agent, 10 to 40 parts of inorganic filler and 0 to 20 parts of other auxiliary agents.
7. The method for preparing an easily slitting anisotropic conductive adhesive film according to claim 1, characterized in that: The method comprises the following steps: mixing the prepared raw materials to form a coating liquid, coating the coating liquid on a protective film, and cutting to obtain anisotropic conductive adhesive films loaded on the protective film.
8. The preparation method according to claim 7, characterized in that: The coating temperature is 65-75°C, and the coating time is 2-10 minutes.
9. The preparation method according to claim 7, characterized in that: The residual solvent rate in the anisotropic conductive adhesive film loaded on the protective film is greater than 4%, and the peeling force between the anisotropic conductive adhesive film and the protective film is greater than 10 gf / inch.
10. The preparation method according to claim 7, characterized in that: The residual solvent rate in the anisotropic conductive adhesive film supported on the protective film is 4.1-8%, and the peeling force between the anisotropic conductive adhesive film and the protective film is 10.1-20 gf / inch.